The Implementation of an Intensive Arabic Language Instruction Program: A Case Study at Al-Aqsa Islamic Boarding School - M. Fauzan Aziz; Astri Mulyati; Zahrotur Rohmah Ramdhani; Idris Syahputra (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to analyze the effectiveness of the intensive Arabic language program at Pondok Modern Al-Aqsha, Jatinangor, West Java, in enhancing students' proficiency in Arabic. The research is grounded in the significance of Arabic language mastery for understanding religious texts in Islamic boarding schools (pesantren). Employing a qualitative method with a descriptive approach, the study involves direct observation, in-depth interviews with teachers and students, and analysis of curriculum-related documents. The findings reveal that the intensive program—which includes lessons in grammar, morphology, conversation, and classical Islamic texts—significantly improves students' communication skills and comprehension of Arabic texts. The communicative teaching methods used, such as simulations, group discussions, audiovisual media, and contextual learning, play a crucial role in accelerating language acquisition. Key factors contributing to the program's success include the dedication of the management and instructors, a well-structured curriculum, and a supportive learning environment. The study recommends optimizing contextual approaches and strengthening continuous evaluation to enhance program effectiveness further. These findings are expected to serve as a reference for other Islamic educational institutions in designing similar intensive Arabic programs.